Physical Layer Security for Edge Caching Wireless Networks - Lin, Xiang; Ng, Derrick W.K.; Schober, Robert; Wong, Vincent W.S. (Wireless Edge Caching: Modeling, Analysis, and Optimization, 2021)
In this chapter, we discuss the application of edge caching to enhance the physical layer security of cellular networks with limited backhaul capacity. By proactively sharing the same content across a subset of base stations (BSs) through both caching and backhaul loading, secure cooperative multiple-input multiple-output (MIMO) transmission of several BSs can be dynamically enabled in accordance with the cache status, the channel conditions, and the backhaul capacity. We formulate a two-stage nonconvex optimization problem for minimizing the total transmit power while providing quality of service (QoS) and guaranteeing communication secrecy during content delivery, where the caching and the cooperative MIMO transmission policy are optimized in an offline caching stage and an online delivery stage, respectively. Caching is shown to be beneficial as it reduces the data sharing overhead imposed on the capacity-constrained backhaul links, introduces additional secure degrees of freedom, and enables a power-efficient communication system design.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Content caching; Optimization; Physical layer security; Quality of service; Video delivery